Empirical Approaches Regarding Interdependency between Technology and Sustainable Tourism - NICOLA-GAVRILĂ, Laura (Journal of Environmental Management and Tourism; Vol 14 No 4 (2023): JEMT, Volume XIV, Issue 4(68), Summer 2023DO - 10.14505/jemt.v14.4(68).25, 2023)
The use of technology has transformed the tourism industry, enabling travelers to search for and book travel online, as well as access information about destinations and activities through websites, social media, and mobile apps. Technology has the potential to promote sustainable tourism practices, while sustainable tourism can, in turn, drive the development and adoption of new technologies. This paper intends to be an overview about empirical approaches regarding the interdependency between technology and sustainable tourism involve studying real-world data and conducting empirical research to understand how technology influences and contributes to sustainable tourism practices. These approaches aim to analyze the impact of technological advancements on various dimensions of sustainability in the tourism industry. Then, it discusses the role of tech and tourism in achieving the goals of sustainable development, identifies different technologies, including data-driven, artificial intelligent, agent-based modeling, that are being used to promote sustainable tourism practices.